Behavioural study of the house cricket (Acheta domesticus) - Hessler Frelinckx, John-Christophe (2019)
The study of personality in species can be used to better understand the dynamics of a population. Personality is however a wide concept and is often divided into easier and identifiable terms when it concerns animalia such as “Behavioural traits”. One such trait is boldness which is often used as a distinguishable trait. In this study boldness is measured in the house cricket (Acheta domesticus). The study aims to measure if boldness is con-sistent in the population or if it has a variation, this is done across a timespan of ten days. Boldness is measured by the latency for a cricket to emerge from a shelter into a novel environment. The study measured boldness for 15 males and 15 females a total of 10 times each every day for a total of 600 predicted observations. The study found that there are distinctive patterns in the levels of boldness in the individuals and that they do differ by significant margins. It can thus be concluded that some crickets are bolder than others and different personality types related to boldness exists. Boldness increased over time as the crickets experienced the trial suggesting plasticity in personality. The study also found that in general males displayed higher degrees of boldness compared to the female crickets.